Evaluation of Socio-economic Factors Affecting Energy Inequality in Iranian Provinces - Ali Asghar Salem; Masoumeh azizkhani (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2022)
Despite the importance of energy inequality issues in Iran, the depth and extent of this issue have been neglected and have not been examined. The necessity of social justice, having an advanced society, and reducing the effects of energy inequality in the economic, social, and cultural growth and development in a country, cause this issue to be investigated. The goal of this study is to identify and evaluate the factors that play an important role in energy inequality. Hence, this study investigated the impact of economic-social parameters on energy inequality by using the combined data method for 31 countries during 2009-2020. This research results show that three factors of population, energy price, and GDP have a negative and significant effect on the inequality of energy consumption. Also, variables such as government current expenditures and education have a significant and positive effect on energy consumption inequality. On the other hand, urbanism and development expenditures of the government have no noticeable relation with energy inequality